2020
DOI: 10.1002/eco.2231
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the relative importance of stock level, river temperature and discharge on the abundance of juvenile Atlantic salmon (Salmo salar)

Abstract: Fisheries scientists need to understand the relationships between river temperature, discharge and production of juvenile salmonids to inform evidence‐based management and regulation of rivers and to understand the potential effects of climate change. These relationships can be determined by characterising interannual variability in abundance and environmental conditions from long‐term monitoring data and assessing their inter‐relationships. Two major challenges are (1) the requirement to separate the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 78 publications
(169 reference statements)
1
35
0
Order By: Relevance
“…Despite these caveats, this analysis identified a high discharge effect between spawning and fry emergence on 0+ salmon and trout densities, consistent with other studies (e.g. Bergerot et al., 2019; Glover et al., 2020), and thereby contributing to the development of a conceptual model of hydro‐ecological processes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Despite these caveats, this analysis identified a high discharge effect between spawning and fry emergence on 0+ salmon and trout densities, consistent with other studies (e.g. Bergerot et al., 2019; Glover et al., 2020), and thereby contributing to the development of a conceptual model of hydro‐ecological processes.…”
Section: Discussionsupporting
confidence: 88%
“…As the number of high discharge events rose from zero to four, the density marginal effect initially decreased from 10 (±6.7) to 9.5 (±6.4), followed by a subsequent increase to 19.9 (±14.3) as the number of high discharge events peaked at 18. Glover, Soulsby, Fryer, Birkel, and Malcolm (2020) showed that high discharges between spawning and emergence enhance 0+ salmon densities. Pre‐emergence covered the river‐specific period from peak autumn to winter adult spawning to spring fry emergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean absolute error was used for discharge to avoid over-emphasis of high flows that can occur when using metrics based on mean squared errors (Krause et al, 2005). It was further used for all isotope simulations given the limited variability in observations and the daily time step of the model (see Gupta et al, 2009;Schaefli and Gupta, 2007). Root mean squared error was otherwise used as this is recommended if no information is available on error distributions (Chai and Draxler, 2004;Kuppel et al, 2018b).…”
Section: Baseline Calibrationmentioning
confidence: 99%
“…The latter question is particularly important in the context of the Girnock Burn, as the catchment is an important long‐term fisheries monitoring site, particularly for Atlantic salmon ( Salmo salar ) (Glover et al, 2020). In Scottish rivers, Atlantic salmon is a key biodiversity component which is also economically important as a sports fishing resource.…”
Section: Introductionmentioning
confidence: 99%